Association between physical activity behavior and quality of life among older adults - Rifky Riyandi Prastyawan; Atikah Rahayu; Sabda Hussain As Shafi; Raditya Akbar Adikara; Adji Pangestu Suhana (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
The aim of this study was to determine whether physical activity and health-related quality of life (HRQL) are associated in apparently healthy older adults. The study design was a cross-sectional study. Measurements were obtained from 164 community-dwelling older adults (52 men and 112 women; 70±8 years, mean±SD), selected using a convenience sampling technique from a community health center in Yogyakarta, Indonesia. Data were collected using a medical history questionnaire, HRQL from the Medical Outcomes Survey short form-36 questionnaire, and physical activity level from the Johnson Space Center physical activity scale. Subjects were separated into low (n=70) and high (n=94) physical activity groups according to the physical activity scale. The higher physical activity group had significantly higher HRQL scores across all eight domains (p<0.05). Compared with the less active group, the more active group had a lower prevalence of hypertension (52% vs. 71%, p=0.030), fewer women (49% vs. 63%, p=0.036), physical function (81±21 vs. 69±20, p=0.031), role physical (82±33 vs. 62±35, p=0.022), vitality (73±16 vs. 60±15, p=0.001), social function (91±19 vs. 84±20, p=0.044), and bodily pain (83±24 vs. 67±22, p=0.001). The two groups did not differ (p>0.05) in terms of mental health, role emotional, or general health. HRQL scores in both physical and mental domains were higher in healthy older adults who consistently engaged in moderate-intensity physical exercise for more than 1 hour per week compared to those who were less physically active. Because this study used a cross-sectional design, these associations should not be interpreted as causal; nevertheless, older adults who are less active or only moderately active may benefit from increasing their physical activity levels to improve their HRQL